INFLUENCE OF SOLUBLE PLACENTAL TISSUE-DERIVED MOLECULES UPON EXPRESSION OF ADHESION MOLECULES BY EA.HY926 ENDOTHELIAL CELLS - O. I. Stepanova; T. U. Lvova; E. N. Purbeeva; M. I. Mirashvili; M. S. Zainulina; S. A. Selkov; D. I. Sokolov (Медицинская иммунология, 2014)
Abstract.  Leukocyte  recruitment  to  placental  tissue  is  an  important  factor  of  its  development.  In  this respect, adhesion molecules at the endothelial cell surface represent a key determining factor of leukocyte adhesion and their trans-endothelial migration. The goal of investigation was to evaluate changed expression of adhesion molecules on the endothelial cells induced by supernates of placental tissue cultures. Placental tissue supernatants produced by the first- and third-trimester placental tissue from normal pregnancy, as well as from women with gestosis, induced higher expression of CD31, CD9, CD62E, CD62P, CD34, CD54, CD51/61, CD49d  and  integrin  β7  expression  by  endothelial  cells,  as  compared  with  their  baseline  levels.  However, the  supernates  from  pre-eclamptic  placental  tissue (3rd  trimester)  caused  an  increased  CD9  expression by  endothelial  cells,  as  compared  with  effects  of placental  supernates  from  eclampsia-free  cases.  Our data  contribute  to  understanding  a  possible  role  of endothelial cell adhesion molecules in recruitment of leukocytes to placental tissue and possible participation of adhesion molecules in pathogenesis of pre-eclampsia. The work was supported by a grant from Russian Ministry of Education and Science ГК №02.740.11.0711 and Presidential grant № НШ-3594.2010.7 and МД-150.2011.7. (Med. Immunol., 2011, vol. 13, N 6, pp 589-596)